Total synthesis of triplinone F - Shet, Manoj N.; Wabale, Krishna R.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2026)
The first total synthesis of triplinone F, along with its C11 epimer, has been executed to establish, inter alia, the stereochemistry of C11 and its complete absolute configuration. The terminal styrene unit was added by cross-metathesis, whereby 1,3-diol units on either side of the central olefin were taken from malic acid enantiomers and coupled by a Yamaguchi alkyne-epoxide opening protocol. The C11 stereochemistry was manipulated by Noyori asymmetric ynone reduction. The Z-selective reduction of alkynoate and acid-catalyzed lactonization forged the right-hand-side 5,6-dihydro-delta-pyrone unit.